Preeclampsia management modalities and perinatal death: a retrospective study in Woldia general hospital - Kenean Getaneh Tlaye; Melese Linger Endalfer; Mesfin Wudu Kassaw; Mussie Mulugeta Gebremedhin; Yared Asmare Aynalem (BMC Pregnancy and Childbirth, 2020)
Abstract Background Hypertensive disorders of pregnancy are among the most common causes of perinatal death. The disorders are highly linked to multiple factors that make prediction and prevention challenging. Early diagnosis and proper management play a crucial role in the wellbeing and life of the women and her baby. In this study, we aimed to assess the association between different management options of preeclampsia and perinatal death at a public hospital in Ethiopia. Methods A document review was conducted on 241 preeclamptic patients’ medical files who have been admitted and delivered in Woldia General Hospital from 2011 to 2016. The study was conducted from August 8 – September 10, 2017 in the aforementioned public hospital in Woldia town, Ethiopia. Associations were tested using Pearson chi squared test and binary logistic regression with a p-value < 0.05 considered significant. Result In this study, nearly 20 every 100 neonates from preeclamptic women has been died and the figure was higher (76.59% Vs 23.4%) among neonates from severe preeclamptic women than mild preeclamptic women (p = 0.01). More than two thirds of the patients (69.3%) received magnesium sulfate to prevent convulsion. Perinatal death among women with diastolic blood pressures greater than 110 mmHg at admission was nearly 3 times (Adjusted Odds Ratio (AOR) = 2.824; 95% Confidence Interval (CI) (1.154–6.038)) higher compared to women with diastolic blood pressures below 110 mmHg. Conclusion In the 5-year period, the magnitude of perinatal death among inpatient preeclamptic women was remarkably high and of which stillbirths exceeded pre-discharge early neonatal death. Utilization of magnesium sulfate tended to increase across years. Maternal diastolic blood pressure at admission was significantly associated with perinatal death.